EFL Students’ Writing Self-Efficacy and Writing Self-Regulated Strategies in Undergraduate Thesis Writing - Hapsari, Astri (Universitas Muhammadiyah Mataram, 2024)
This study attempts to map undergraduate students’ writing self-efficacy and writing self-regulated learning strategies in the process of writing their undergraduate thesis. This survey study was conducted in Thesis Proposal Writing coursework in a private university in academic year 2022/2023. Eighty-six students agreed to participate in this study by filling out a questionnaire, and eight students were interviewed to obtain more information about their responses to the questionnaire. The findings indicate that the students’ writing self-efficacy were categorized into medium (M=4,7872, SD=1,138), which means they believe either maybe or basically can do the writing ability stated in the items. They were relatively more efficacious in the use of English writing (M=4,936, SD=1,199), but less efficacious in grammar and spelling (M=4,69, SD=1,062). In terms of writing self-regulated strategies, most students sometimes used writing self-regulated strategies; the most frequently used SRL strategies were self-consequences strategies (M=2,41; SD=0,641) and self-evaluation strategies (M=2,35; SD=0,693) while the least frequently used strategies were self-monitoring strategies (M=1,755, SD=0,793). From these findings, the author suggests that students should be supported to enhance their writing self-efficacy and self-regulated learning strategies by providing more cohesive and coherent written corrective feedback. By doing so, they will be more efficacious in terms of ideation, organization, grammar, and spelling in writing their undergraduate thesis. It will also enhance their behavioral self-regulated learning strategies in the domain of self-monitoring strategies